EFEK SAMPING AKSEPTOR KONTRASEPSI SUNTIK 3 BULAN DI BPS NY SUHARTATIK, Amd. KebMOJOKERTO - Eka Prameswari, Veryudha; Nur Ajizah, Hanik (JURNAL KEPERAWATAN SEHAT, 2016)
Hormonal contraception is a type of contraception that is most widely used by family planning acceptors are injectable contraceptives. Injectable contraceptive method is considered one of the contraceptive methods that have a high level of effectiveness, the price is relatively cheap, so affordable to the community, its use is also easy and practical. Each method of contraception has side effects, as well as injectable contraceptives. In the majority of users of injectable contraceptives, side effects occur are menstrual disorders, those who experience weight gain. The purpose of the research is to identify menstrual disorders and weight gain in the 3 month injectable contraceptive acceptors. Research design uses descriptive method. The population research is the entire 3 month injectable contraceptive acceptors as many as 238 people. The sample in this research of 68 people, who were taken in consecutive sampling. The research results that the side effects that are often experienced by the 3 month injectable contraceptive acceptors in Bps Mrs. Suhartatik, Amd Keb is menstrual disorders as many as 44 people (64.7%), while having less weight change as many as 39 people (57.4%). Midwives should improve the management of obstetric care in family planning, providing comprehensive planning services, by providing counseling on side effects in the 3 month injectable contraceptives and how to overcome them.Keywords: Acceptors, Side effects, Contraception